Hiazm v strukture slavjanskoj frazy: predposylki, funkcii i sledstvija - Norman, Boris Justinovič (Slavistična revija, 2001)
The article discusses the chiasmus, i.e., syntactic switch of the type A person does not live in order to eat but eats in orede to live, which is common in puns, aphorisms, proverbs, etc. It analyzes some consequences of the chiasmus, e.g., the loosening of connections between individual syntactic positions and semantic properties of words. The examples from some Slavic language (Russian, Bulgarian, Polish) demonstrate the dependence of this procedure on the linguistic principles of individual language (word order, presence of case forms, etc.).
Keywords: besedni red; hiazem; sintaksa; Slavic languages; slovanski jeziki